Implementation of independent character in children with special needs in basic education units - Lisa Retnasari; Ervi Nur Melisa; Aim Abdulkarim (Global Econedu, 2024)
This article addresses the crucial issue of instilling independent character in children with special needs, recognizing their unique circumstances that necessitate tailored attention, particularly in the realm of education. The primary objective of the study is to delineate the process of fostering independent character in these children and to identify factors that either hinder or facilitate its implementation at SD Negeri Karanganyar Yogyakarta. Employing a qualitative descriptive approach, the research relies on observation, interviews, and documentation as data collection methods, with school principals and special accompanying teachers as the subjects. The focal point is the examination of independent character implementation in children with special needs at SD Negeri Karanganyar. The study reveals a three-stage approach to instill independent character, encompassing collaborative preparation involving teachers and parents, an implementation phase featuring habituation and internalization in learning and daily activities, and an evaluation stage conducted every three months in the middle of the semester. Supporting factors include parental involvement, school collaboration, and adequate facilities while inhibiting factors comprise insufficient parental awareness and inadequate infrastructure. The findings contribute valuable insights to the enhancement of independent character development in children with special needs, emphasizing the pivotal role of collaborative efforts and addressing existing challenges in education and parental involvement.